2013
DOI: 10.1210/me.2012-1212
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Function of Estrogen Receptor α in Smooth Muscle and Fibroblast Cells in Prostate Development

Abstract: Estrogen signaling, through estrogen receptor (ER)α, has been shown to cause hypertrophy in the prostate. Our recent report has shown that epithelial ERα knockout (KO) will not affect the normal prostate development or homeostasis. However, it remains unclear whether ERα in different types of stromal cells has distinct roles in prostate development. This study proposed to elucidate how KO of ERα in the stromal smooth muscle or fibroblast cells may interrupt cross talk between prostate stromal and epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Early reports showed that ERα in stromal cells could affect the prostate development [ 25 , 26 ]. Another report showed that E2 plus testosterone treatment could stimulate the PCa initiation [ 27 ], however, the role of stromal ERα in the later stages of PCa progression and how it may affect immune cell infiltration and PCa metastasis is not well studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early reports showed that ERα in stromal cells could affect the prostate development [ 25 , 26 ]. Another report showed that E2 plus testosterone treatment could stimulate the PCa initiation [ 27 ], however, the role of stromal ERα in the later stages of PCa progression and how it may affect immune cell infiltration and PCa metastasis is not well studied.…”
Section: Resultsmentioning
confidence: 99%
“…In prostate development, using Cre-loxP gene knockout strategy, reports have shown that ERα plays different roles in prostate epithelial as well as different types of prostate stromal cells [ 26 , 49 ]. In the PCa mouse models, both ERα knockout [ 50 ] and ERα agonist treatment [ 51 ] showed mice with activated ERα can develop high-grade PIN, suggesting ERα might play important roles in PCa progression.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the in vivo role of ERα in BCa development, we employed cre-loxP strategy to knock out the floxed ERα gene (ERαKO) [ 34 - 36 ]. The breeding scheme for the generation of CMV-ERαKO (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This interaction is mediate by ERα, which is a receptor that acts in the muscle cells and fibroblasts, and influences the proliferation of epithelial cells (Vitkus et al . ). Our data showed an increase in ERα immunoreactivity in stromal cells and the cytoplasm of epithelial cells in the prostates from male and female senile gerbils that were exposed to EE.…”
Section: Discussionmentioning
confidence: 97%